Price Control at the Retail Level - Morris, Bruce R. (Quarterly Journal of Economics, 1944)
Journal Article Price Control at the Retail Level Get access Bruce R. Morris Bruce R. Morris Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 58, Issue 2, February 1944, Pages 323–324, https://doi.org/10.2307/1883323 Published: 01 February 1944